Antenatal steroids and thyroid hormone function in preterm infants. (November 2018) - Kaluarachchi, Dinushan; Zhao, Qianqian; Colaizy, Tarah
Abstract Background Antenatal steroids (ANS) are used widely for women at risk of preterm delivery. Evidence on the effects of ANS on thyroid hormone function in preterm infants is limited. Objectives To determine effects of ANS on thyroid hormone function in preterm infants. Methods A retrospective cohort study of preterm infants born before 30 weeks of gestation. Infants were divided into no ANS, partial ANS, and complete ANS groups. Thyroid function tests at day of life 30 were compared. Results 260 Infants were included. A significantly higher proportion of patients were started on levothyroxine (LT4) in no ANS group and partial ANS group compared to complete ANS group. Logistic regression analysis revealed that infants in no ANS group are more likely to have TSH > 6 μIU ml−1 and started on LT4 compared to complete ANS group. Conclusion Infants in no ANS group are more likely to have thyroid dysfunction compared to complete ANS group.